STUDENTS VIEWS ON THE IMPLEMENTATION OF 16 COURSEWORK CUT-OFF POINT AT UNIVERSITY - Pinto Owino; Joyce Nemes (International Journal of Economy, Education and Entrepreneurship, 2023)
The purpose of this study was to explore the current practice when implementing coursework cut-off point (CWCP) to undergraduate students in the Dodoma region of Tanzania, specifically at the University of Dodoma. The mixed approach was employed with the help of convergent research design. The study involved 379 undergraduate students, the respondents were selected through simple random and purposive sampling. Furthermore, data were collected through questionnaire and semi-structured interview. Quantitative data were analyzed through descriptive statistics and presented in frequency and percentage while qualitative data were analyzed thematically. The results that most of students were positive minded on the use of 16 CWCP for enhancing students learning at the university